Estudio y valoración de los “Mitos y Leyendas” como riqueza cultural intangible del Cantón Babahoyo de la Provincia de los Ríos - Fernández Enríquez, Génesis Abigail (2016)
The report of Study and evaluation of the "myths and legends" as an intangible cultural wealth of the Babahoyo catalog of the Province of the Rivers was with scientific bibliographical means and visits in situ, using tools such as interviews with citizens of the canton, which allowed obtaining Data for the elaboration of the approach of the problem and the possible solutions, in a respective way the suggested proposal. With the proposed proposal to carry out a study of the valuation of myths and legends as an intangible cultural richness of the Babahoyo canton Province of Los Ríos, the rescue of the oral tradition of the same would be encouraged, making this a place of cultural tourist attraction. It has the respective conclusions as an analysis of the study and the recommendations as strategies that will serve to achieve the present study, this with the support of the respective theoretical scientific foundation that helped to corroborate the knowledge of the interviewees